STING activation in alveolar macrophages and group 2 innate lymphoid cells suppresses IL-33–driven type 2 immunopathology - Li She; Gema D. Barrera; Liping Yan; Hamad H. Alanazi; Edward G. Brooks; Peter H. Dube; Yilun Sun; Hong Zan; Daniel P. Chupp; Nu Zhang; Xin Zhang; Yong Liu; et al. (JCI Insight, 2021)
2′3′-cGAMP is known as a nonclassical second messenger and small immune modulator that possesses potent antitumor and antiviral activities via inducing the stimulator of IFN genes–mediated (STING-mediated) signaling pathway. However, its function in regulating type 2 immune responses remains unknown. Therefore, we sought to determine a role of STING activation by 2′3′-cGAMP in type 2 inflammatory reactions in multiple mouse models of eosinophilic asthma. We discovered that 2′3′-cGAMP administration strongly attenuated type 2 lung immunopathology and airway hyperreactivity induced by IL-33 and a fungal allergen, Aspergillus flavus. Mechanistically, upon the respiratory delivery, 2′3′-cGAMP was mainly internalized by alveolar macrophages, in which it activated the STING/IFN regulatory factor 3/type I IFN signaling axis to induce the production of inhibitory factors containing IFN-α, which blocked the IL-33–mediated activation of group 2 innate lymphoid (ILC2) cells in vivo. We further demonstrated that 2′3′-cGAMP directly suppressed the proliferation and function of both human and mouse ILC2 cells in vitro. Taken together, our findings suggest that STING activation by 2′3′-cGAMP in alveolar macrophages and ILC2 cells can negatively regulate type 2 immune responses, implying that the respiratory delivery of 2′3′-cGAMP might be further developed as an alternative strategy for treating type 2 immunopathologic diseases such as eosinophilic asthma.